Dimensions for a scale to evaluate the initial responses by organisational leaders against the pandemic - Bilgehan Bozkurt (Humanities & Social Sciences Communications)
Abstract Although there is a need for empirical studies to examine pandemic leadership, the existing scales of leadership assessment are controversial. The purpose, here, is to propose dimensions that could set foundations for an “organisational leadership evaluation scale” that evaluates the scientific significance of initial responses by organisational leaders against “the novel Coronavirus pandemic”. The research question is a practical one: “How can organisational leaders lead their organisations as a pandemic that has just started is increasingly raising concerns on health?”. Review research and a systematic review of the pre-pandemic publications about leadership, organisation, pandemic and health among various electronic scientific databases (e.g., Web of Science, Scopus, etc.) motivate new knowledge. The dimensions of what would have been a significant initial response to the pandemic are broadly emphasising health, having a global understanding, recognising competencies, not losing control and prioritising trust. These gender-neutral and style-free dimensions could form the dimensions of an “organisational leadership evaluation scale”. To perform, there is a need to support learning and “depth of knowledge” and to oppose superficiality, “convenience information” and “knowledge deficit”.